TANGGUNG JAWAB PEJABAT PEMBUAT TANAH DALAM MEMBUAT AKTA OTENTIK YANG PENGHADAPNYA MENGGUNAKAN IDENTITAS DAN TANDA TANGAN PALSU (STUDI KASUS PUTUSAN NOMOR 412/PDT/2018/PT.DKI) - febyola berylani sugiarto; Mella Ismelina F.R. (Fakultas Hukum Universitas Tarumanagara, 2021)
This thesis discusses the responsibilities of PPAT, which the party uses a fake identity and signature based on an example of a case on the DKI Jakarta High Court Decision Number 412 / PDT / 2018 / PT.DKI. The main problem in this research is about the PPAT's responsibility if there is a fake identity and signature of the actor in the deed he makes and what is the position of the authentic deed. This research is a type of normative research with a prescriptive type of research. The results showed that PPAT can be held accountable because it is not careful in carrying out its duties. PPAT responsibilities can be in the form of administrative, civil, and even criminal areas. The status of the authentic deed made by PPAT which contains false information contains legal flaws because it does not meet the validity requirements of an objective element agreement, namely related to a lawful cause so that the sale and purchase certificate becomes null and void by law.